The income elasticity of healthcare spending in Turkey - Uçar, Yavuz Selim. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
In this paper, we present the income elasticity of spending on healthcare services in Turkey, and analyze the effect of healthcare reforms and 2008 global financial crisis on the elasticities. We estimate the elasticities by using data from households’ out-ofpocket health expenditures between 2006 and 2019 and by utilizing two-part models and the quantile regression model. The elasticity results show that health is a highly elastic good in Turkey. In addition, the effect of the crisis remains significant through different quantiles of health expenditure. We also notice that after the crisis was over and the income of households started growing, due to increases in expenses of patient care services, the ratio of expenditure spent on pharmaceutical products shrunk too much and left its place to other categories, primarily outpatient care.
Keywords: Medical care -- Turkey.; Health services administration -- Turkey.; Health care reform -- Turkey.; Income -- Econometric models.